Mathematical-physical description of the oxygen-inhibited layer (OIL) in nanofilled dental polymers = Descripción físico-matemática de la capa inhibida por oxígeno en polímeros dentales nano rellenados - Ferreto Gutiérrez, Isabel 1974-; Hernández Mata, Alejandra 1970- (2024)
This research evaluates the presence of the oxygen-inhibited layer (OIL) on the top surface of a photopolymerized dental composite resin protected with a glycerin layer. This evaluation was conducted using physical and mathematical methods. Polymerized discs were fabricated to evaluate Vickers microhardness (VHN), and pre-and post-polymerized samples were used for the calculation of C-O/C-H ratios through Fourier Transform Infrared Spectroscopy (FTIR) (n=10), using two types of glycerin, one for medical use (MG) and another for dental use (DG). Surface hardness decreased from MG to DG to CO, and the increase in C-O/C-H ratios decreased in the same order (p<0.05). Samples protected with medical and dental glycerin layers are harder and exhibit lower C-O/C-H bond ratios than the control group.
La presente investigación evalúa la presencia de la capa inhibida por oxígeno OIL en la última superficie fotocurada de una resina compuesta de uso odontológica que fue protegida con una capa de glicerina. Esta evaluación se hizo a partir de métodos físicos y matemáticos. Se fabricaron discos polimerizados para evaluar la microdureza Vickers (VHN) y pre y post polimerizados para el cálculo de tasas C-O/C-H por medio de Espectroscopía Infrarroja Transformada de Fourier (FTIR) (n=10) usando dos tipos de glicerina, una de uso médico (MG) y otra de uso dental (DG). La dureza superficial disminuyó de MG a DG a CO y el aumento de tasas C-O/C-H disminuyó en ese mismo orden (p<0,05). Las muestras protegidas con capas de glicerina médica y odontológica son más duras y presentan menos cantidad tasas de enlaces C-O/C-H que el grupo control.
En revista Odóvtos, vol. 26, no.1 (enero-abril 2024)
Descripción basada en el contenido visto el 22 de enero, 2025
También disponible en formato HTML y EPUB